Dust suppressant treatments. Quality control - Valenzuela T., Pamela; H. Palma G, Juan; Vega S, Sergio (Revista de la Construcción. Journal of Construction, 2014)
Dust emissions by wind effect from mining deposits or industrial waste and passing vehicles on unpaved roads, is a problem that affects the productive activities; the environment and the health of those who remain in the contaminated area. The social sensitivity and environmental requirements on this issue in Chile have increased, as well as offering different suppressors and application technologies. Have been reviewed the causes of dust emission and technologies available in Chile for dust suppression, plus methodologies and standards for assessing the performance of the treated materials with different suppressors. In some cases it is not possible to compare performance properties such as durability, application dose and frequency of applications, among others aspects. The procedures described in the NCh 3266-2012 standard allows the assessment of wind erosion in waste deposits, vacant lots and unpaved roads, among others, along with evaluating the performance of different types of dust suppressants from comparable objective data. This allows selecting the most suitable suppressor, improve efficiency of treatments, optimize costs and improve production processes.